Integrated Energy System Optimal Dispatch Considering Oxy-Fuel Combustion Carbon Capture Technology and Source-Load Bilateral Response - Haizhu YANG; Yanan BAI; Peng ZHANG; Zhongwen LI (Zhongguo dianli)
In order to reduce the carbon emission level of gas turbines and improve their flexibility, this paper proposes a low-carbon economic optimization strategy for the integrated energy system that takes into account oxy-fuel combustion carbon capture technology and source-load bilateral response. Firstly, the operating principle and energy flow characteristics of oxy-fuel combustion technology were studied, and a coupling model of air separation oxygen production equipment and carbon capture equipment was constructed. Secondly, the adjustable heat-to-power ratio was introduced as a supply-side response strategy, and a comprehensive trade-off was made for the demand-side between the characteristics of electricity, heat energy and gas load, and a demand-side response mechanism was formed with the guidance of energy prices and considering their substitutable attributes with each other. Finally, through constraining the carbon emissions by tiered carbon trading with consideration of carbon emissions of gas load, the units output in each period was optimized with the system operating cost as the objective. Multiple scenarios were set up for simulation analysis, and the results show that the oxy-fuel combustion carbon capture technology can effectively reduce the carbon emissions of the system, and the source-load bilateral response can flexibly adjust the energy supply relationship between the supply side and the demand side, and effectively reduce the operating cost of the system.